Pembangunan Desa Berkelanjutan Melalui Edukasi dan Inovasi Pengelolaan Sampah Rumah Tangga Di Desa Dawan Klungkung - I G. A. N Alit Sumantri; I Gusti Agung Ayu Pramita Indraswari; Putu Pande R. Aprilyani Dewi; Ni Putu Budiadnyani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Household waste management is a crucial issue in realizing sustainable village development, especially in rural areas such as Dawan Village, Klungkung. Lack of public awareness of the importance of proper waste sorting and processing has resulted in environmental pollution and low economic value of household waste. This community service activity aims to increase community capacity in managing household waste through an educational and innovative approach based on community participation. The implementation method includes socialization, training in sorting organic and inorganic waste, and training in recycling into creative products such as eco-bricks and compost. The results of the activity showed an increase in community knowledge about waste management, the formation of environmental care groups, and the creation of products with economic value from household waste. This activity proves that with the right education and innovation that is appropriate to the local context, household waste management can be an important pillar in supporting sustainable and environmentally friendly village development.